Evaluation of undergraduate medical students at a government medical college in Patna (Bihar), for depression and related factors - a cross-sectional study - Sinha, Pragya; Singh, Pankhuri (International Journal Of Community Medicine And Public Health, 2025)
Background: Medical curriculum can be both mentally and physically taxing. While depression can strike anyone at any time, research has shown that medical students experience depression at a higher rate than their age-matched peers. The lack of mental health screening regimes for students significantly contribute to the paucity of information regarding their mental wellness and necessitates conduction of studies for their mental health evaluation. Methods: A cross-sectional study was conducted in a government medical college and undergraduate students were screened using the 9-item patient health questionnaire (PHQ-9) and a structured questionnaire, for depression and its associated factors respectively. A cut-off score of 10 was used to define depression in this study at which respondents were most likely to meet diagnostic and statistical manual of mental disorders, 4th edition (DSM IV) criteria for major depressive disorder (likelihood ratio ≥7.1). Results: A total of 368 students responded to the survey questionnaire. 49.4% (124/251) male and 44.4% (52/117) female students had a score ≥10. There was a 47.8% (176/368) prevalence of depression indicating additional clinical evaluation. As the year of MBBS study increased, the number of depressed students increased; with a significant association between them. Risk factors such as stress due to impending PG entrance exams, body image dissatisfaction (BID) and insufficient time for leisure activities had significant association with depression. An alarming 70.1% (258/368) of the students screened expressed reluctance to seek mental health care services. Conclusions: Regular evaluations, awareness campaigns and student counsellors could be of great assistance to students in addressing their concerns, hesitation and stigma.